Patient Participation in Patient Safety and Its Relationships with Nurses' Patient-Centered Care Competency, Teamwork, and Safety Climate - Jee-In Hwang; Sung Wan Kim; Ho Jun Chin (Elsevier, 2019)
Purpose: This study's aim was to examine degrees of patient participation in patient safety activities in hospitals and to investigate their relationships with nurses' patient-centered care competency (PCC), teamwork, and safety climate. Methods: A cross-sectional study design was used. Data were collected with 479 nurses from two general hospitals in Seoul, Korea, using a questionnaire designed to collect data on patient participation in patient safety activities, PCC, teamwork perceptions, and safety climate. The response rate was 74.1% (N = 355). Data were analyzed using descriptive statistics and multiple logistic regression analysis. Results: The mean score for patient participation was 2.76 ± 0.46 of 4.0. The mean scores for PCC, teamwork, and safety climate were 3.61 ± 0.46, 3.64 ± 0.41, and 3.35 ± 0.57 of 5.0, respectively. Nurses who experienced high patient participation in patient safety activities (≥ 3.0) had higher scores for PCC, teamwork, and safety climate. Multiple logistic regression analysis revealed that PCC (OR = 2.31, 95% CI = 1.14-4.70) and safety climate (OR = 2.51, 95% CI = 1.09-5.78) scores were the significant factors associated with patient participation. Conclusion: The degree of patient participation in patient safety activities was not high. Nurses' PCC, teamwork, and safety climate were positively related with patient participation. In particular, the findings indicate that enhancing nurses' competency for patient-centered care and creating a strong safety climate are important to promote patient participation for safer health care. Keywords: culture, patient-centered care, patient participation, patient safety